Sikap Bahasa Gen Z di Denpasar Terhadap Bahasa Indonesia - Ni Ketut Veri Kusumaningrum; Ni Putu Veny Narlianti; Elsita Lisnawati Guntar; Ni Nyoman Widani (Journal Innovation In Education, 2025)
This study examines the language attitudes of Generation Z in Denpasar towards Indonesian in the context of a trilingual environment that includes Balinese, Indonesian, and a foreign language. Using mixed methods, the study involved 100 respondents selected through random sampling techniques. Data were collected using a questionnaire with a 5-point Likert scale to measure cognitive, affective, and conative aspects, as well as participatory observation in the social environment of Gen Z in Denpasar. The results showed that Gen Z in Denpasar has a positive attitude towards Bahasa Indonesia, even though they live in a multilingual environment. The majority of respondents use Indonesian as the main language in the context of learning and formal communication. However, there are variations in language use according to the social context and communication situation. Factors influencing their language attitudes include the education system, the influence of social media and the internet, the development of the tourism industry, and the dynamics of local and national identity. This research provides important insights into language use trends and challenges in national language maintenance in the digital era, and can serve as a basis for developing more effective language policies.